Long-Run Forecasting of Emerging Technologies with Logistic Models and Growth of Knowledge - Kucharavy, D.; Schenk, E.; De Guio, R. (Cranfield University Press, 2009)
In this paper applications of logistic S-curve and component logistics are considered in a framework of longterm forecasting of emerging technologies. Several questions and issues are discussed in connection with the presented ways of studying the transition from invention to innovation and further evolution of technologies. First, the features of a simple logistic model are presented and diverse types of competition are discussed. Second, a component logistic model is presented. Third, a hypothesis about the usability of a knowledge growth description and simulation for reliable long-term forecasting is proposed. Some interim empirical results for applying networks of contradictions are given.
Organised by: Cranfield University
Keywords: Component logistic model; Innovation process; Knowledge acquisition; OTSM-TRIZ